Case-term Adverse Outcomes of Chronic Hepatitis C, Extrahepatic Manifestations of a Young Man Infected in Early Childhood - S. V. Baramzina; A. L. Bondarenko (LLC "Diagnostics and Vaccines", 2015)
In the present article discusses the clinical case of unfavorable course of chronic hepatitis C with the outcome of cirrhosis and development of extrahepatic manifestations of a young man of 20 years as a result of infection in early childhood.